A RARE CASE OF UNILATERAL ADRENAL LYMPHOMA WITH LYMPHADENOPATHY - Brabavathi; YS, Ng; CV, Tong (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Adrenal lymphoma is an extremely rare and highly invasive malignant disease. We report a rare case of unilateral adrenal lymphoma with lymphadenopathy. CASE A 68-year-old male presented with abdominal discomfort, polyuria and weight loss of 15 kg over 6 months. Physical examination revealed a thin elderly man with fullness over the left lumbar and inguinal lymph nodes. Laboratory tests showed markedly elevated lactate dehydrogenase (LDH) levels of >690 UI/L (<248) and hypercalcemia. A computed tomography (CT) scan revealed a large left adrenal mass (11.6 x 8.3 x 9.6 cm) with multiple matted abdominal lymph nodes, raising a suspicion of adrenal malignancy. Following this, hormonal profile was done which showed normal cortisol and catecholamines. An ultrasound-guided trucut biopsy of the right inguinal lymph nodes was performed. The microscopic examination showed a malignant tumour composed of mononuclear cells with pleomorphic nuclei with high mitotic figures. On immunohistochemistry, the tumour cells were positive for vimentin, CD20, CD10, BCL-6, leucocytes common antigen (LCA) and Ki67 proliferating index was 60% in the tumour cells. A diagnosis of diffuse large B cell lymphoma (DLBCL) was made. The patient was referred to the haematology team and started on chemotherapy. CONCLUSION Primary adrenal lymphoma is a rare entity with a generally poor prognosis. They usually involve both adrenal glands, but unilateral adrenal involvement can occur in about one-third of patients. In patients with large adrenal masses and constitutional symptoms, the initial dilemma is to differentiate between adrenal carcinoma versus other forms of malignancies or chronic infections. Adrenal biopsy is generally avoided in suspected adrenal carcinoma as it may be harmful because it can lead to tumour seeding. In our patient, the presence of multiple lymphadenopathy which was accessible for biopsy helped clinch the diagnosis of adrenal lymphoma. The presence of lymphadenopathy with large adrenal masses, even if unilateral, should prompt suspicion of the diagnosis of adrenal lymphoma.